Avaliacao da necessidade da dosagem rotineira de hematocrito, hemoglobina, ureia e creatinina sericos durante a avaliacao pre-anestesica - Nascimento P., Jr [UNESP]; Kirsch, L. A. [UNESP]; Samaha, J. T. [UNESP]; Castiglia, Yara Marcondes Machado [UNESP] (My University, 1998)
Background and Objectives - There are many questions and opinions about the value of routine preoperative tests as an integral part of the preanesthetic evaluation. Current trends suggest that such tests should be based on detailed clinical and physical evaluation. Since such tests are still routinely performed and questions about their real value still persist, the aim of this study was to assess the value of routine hematocrit (Ht), hemoglobin concentration (Hb), blood urea nitrogen (BUN) and serum creatinine results in patients undergoing elective surgery, to establish when they are needed and aiming at answering such questions. Methods - 1065 patients aged 12 years and above, physical status ASA I, II and III, scheduled for elective surgery were studied. Patients were divided into 7 different age groups with randomized distribution of gender. Ht, Hb, BUN and serum creatinine results, routinely asked by our surgical departments, were observed and analyzed. Variance Analysis was used for each variable, and the Bonferroni Multiple Comparison Test was used to compare group to group. Differences were considered significant when p < 0.05 (5%). Results - For all patients, 4025 laboratory tests were obtained. The number of tests was the same for each group. There were no differences in Ht and Hb values which remained within normal ranges. Considering BUN and serum creatinine, there was a difference between younger and older patients, but the results were normal in all groups. Conclusions - We concluded that mean Ht, Hb, BUN and serum creatinine values in all age groups were all acceptable for surgical patients in general. However, they are barely useful if performed regardless of clinical evaluation. Thus, such preoperative routine tests should be abandoned and the good clinical practice with common sense should prevail in indicating them.
Assessment of the need for routine dosage of hematocrits, hemoglobin, blood urea nitrogen and serum creatinine during preoperative evaluation
Keywords: Laboratory tests: creatinine, hematocrit, hemoglobin, urea; Preoperative evaluation; creatinine; hemoglobin; urea; creatinine blood level; hematocrit; hemoglobin determination; human; major clinical study; preoperative evaluation; urea nitrogen blood level